The Role of Marketing Intelligence in Achieving Strategic Ambidexterity: An Analytical Study of the Opinions of a Sample of Managers of Telecommunications (Internet) Companies in the Kurdistan Region - Iraq - Faridun Abdulla, Daroon; Omer Hasan, Ghazi (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This research aims to analyze the relationship and the impact between marketing intelligence with its dimensions (customer understanding, market understanding, product intelligence, competitor intelligence) and strategic ambidexterity represented by (exploring opportunities, exploiting opportunities, structural ingenuity) in (27) Internet companies in the Kurdistan region - Iraq. After reviewing a set of studies and literature, theoretical concepts and model building and hypotheses were written based on the dimensions of marketing intelligence as well as strategic ambidexterity, and based on the nature of the research and the goals that it seeks to achieve, it has been relied on the descriptive analytical approach. In order to collect data, a questionnaire was applied, (462) questionnaires were distributed directly and electronically through (Google Form) to all members of society represented by heads of units, administrative departments and supervisors in Internet companies in the Kurdistan region - Iraq, which numbered (542) managers in all companies according to the company’s documents during the research. After sorting the received forms directly and checking them, the number of questionnaires valid for analysis reached (219), in addition to (146) questionnaires electronically, so that the number of total forms valid for statistical analysis reached (365) questionnaires. Several statistical methods were used, including arbitrators and Cronbach’s alpha to verify validity and reliability, simple correlation coefficient and regression using the (SPSS-26) program. The results showed a positive correlation and impact between the research variables and its dimensions. Based on the results of the research, a number of recommendations were presented related to the need to focus companies operating in the telecommunications sector (internet) on their adoption to marketing intelligence dimensions in order to achieve the strategic ambidexterity of the surveyed companies.